UPAYA HUKUM PENYELESAIAN SENGKETA ANTARA KONSUMEN DENGAN PENGEMBANG PT. NAJAH BINTANG SEJAHTERA DI KOTA PEKANBARU - Wirawan, Dwi Weka; Yulfasni, Yulfasni; Mannas, Yussy Adelina (Alhurriyah, 2019)
House buying and selling is very vulnerable and problems often occur to cause disputes, This research was conducted in an empirical juridical way, the nature of descriptive analysis was by qualitative data analysis, The absence of consumer understanding of the buying and selling process in a contract carried out with the developer and there are still those who do not understand the contents of a contract and there are still developers with consumers making agreements under the hand that are not in accordance with the Laws and Regulations, Housing developers must be responsible for losses suffered by consumers, The legal effort that can be made by consumers is by taking a solution in a way outside the court of non-litigation and litigation through the general court, Consumer dispute resolution is first resolved by means of consensus agreement or peacefully if there is no further settlement, it can be done through a way of settlement outside the court (non litigation) or through a public court (litigation) either civil or criminal.Â